1993
DOI: 10.1149/1.2056098
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of Thin Interfacial SiO2 Layers in Directly Bonded Czochralski and Float‐Zone Silicon Wafer Pairs

Abstract: The stability of thin interfacial SiO2 layers in directly bonded silicon wafer pairs is investigated by means of high‐resolution transmission electron microscopy. The results are explained by using a classical nucleation theory. It is shown that the interfacial oxide layers in bonded Czochralski (CZ) grown silicon wafer pairs is structurally more stable than those in bonded float‐zone (FZ) silicon wafer pairs. The effect of internal diffusion of the oxygen atoms in the silicon wafers on the interfacial oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…[1][2][3][4] SiO 2 films can be deposited by evaporation, sputtering, sol-gel, chemical vapor deposition, and other methods. [1][2][3][4] SiO 2 films can be deposited by evaporation, sputtering, sol-gel, chemical vapor deposition, and other methods.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] SiO 2 films can be deposited by evaporation, sputtering, sol-gel, chemical vapor deposition, and other methods. [1][2][3][4] SiO 2 films can be deposited by evaporation, sputtering, sol-gel, chemical vapor deposition, and other methods.…”
Section: Introductionmentioning
confidence: 99%
“…SOI substrates fabricated by SIMOX (separation by implanted oxygen) are typically subjected to internal thermal oxidation (ITOX) anneals to thicken buried oxides formed by high dose oxygen ion implantation (6,7). In the context of Si wafer bonding, the thermal stability of thin (1 -10 nm) interfacial oxides between bonded wafer surfaces has been examined as a function of Si wafer doping, Si wafer growth method (float-zone (FZ) or Czochralski (Cz)), and Si wafer surface orientation (7)(8)(9)(10). It was concluded that dissolution of native oxides having a thickness >1 nm is not possible with annealing at temperatures in the range 1100 -1200 o C, and that undesirable oxide islanding is typical, especially with Cz wafers.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 In the context of Si wafer bonding, the thermal stability of thin ͑1-10 nm͒ interfacial oxides between bonded wafer surfaces has been examined as a function of Si wafer doping, Si wafer growth method ͓float-zone ͑FZ͒ or Czochralski ͑CZ͔͒, and Si wafer surface orientation. [7][8][9][10] It was concluded that dissolution of native oxides having a thickness Ͼ1 nm is not possible with annealing at temperatures in the range of 1100-1200°C and that undesirable oxide islanding is typical, especially with CZ wafers. In con-trast to these results, it was shown 4 that a few monolayers of interfacial oxide could be made to disappear in FZ wafers after annealing at 1150°C.…”
mentioning
confidence: 99%